2011
DOI: 10.1088/0004-637x/736/2/142
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Driven Implosion and Triggered Star Formation

Abstract: We present simulations of stable isothermal clouds exposed to ionizing radiation from a discrete external source, and identify the conditions that lead to Radiatively Driven Implosion and Star Formation. We use the Smoothed Particle Hydrodynamics code SEREN (Hubber et al. 2010) and the HEALPix-based photoionization algorithm described in Bisbas et al. (2009). We find that the incident ionizing flux is the critical parameter determining the evolution; high fluxes disperse the cloud, whereas low fluxes trigger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 40 publications
8
140
0
1
Order By: Relevance
“…Numerical simulations show that photo-ionisation from massive stars inside molecular clouds generally leads to a slight decrease in the global star formation efficiency, with gas expulsion partly compensated for by triggered star formation (e.g., Dale et al 2012a,b). Nevertheless, they show that triggered star formation does occur, and amounts to a few% of the total cloud mass (see also Walch et al 2011). Dale et al (2012b) find that the association of young stars with gas structures such as shells or pillars, as occurs in NGC 6357, is a good but not conclusive indication of triggered star formation.…”
Section: Star Formation On the Smaller Scale: From Gas To Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations show that photo-ionisation from massive stars inside molecular clouds generally leads to a slight decrease in the global star formation efficiency, with gas expulsion partly compensated for by triggered star formation (e.g., Dale et al 2012a,b). Nevertheless, they show that triggered star formation does occur, and amounts to a few% of the total cloud mass (see also Walch et al 2011). Dale et al (2012b) find that the association of young stars with gas structures such as shells or pillars, as occurs in NGC 6357, is a good but not conclusive indication of triggered star formation.…”
Section: Star Formation On the Smaller Scale: From Gas To Starsmentioning
confidence: 99%
“…The elephant trunk with IRS 4 at the tip inside G353.2+0.9 suggests that the so-called "radiation-driven implosion" (see Bisbas et al 2011 and references therein) may be under way. When an ionisation front crosses a dense clump, it generates a shock which compresses the clump making it collapse under some conditions.…”
Section: Star Formation On the Smaller Scale: From Gas To Starsmentioning
confidence: 99%
“…It was shown that under zero ionizing flux, a prolate cloud in interstellar background radiation field either collapsed to a spindle or dispersed into space, depending on its initial conditions (Nelson & Langer 1998). The recent work by Bisbas et al (2011) proved that ionizing flux between 10 9 and 10 11 cm −2 s −1 can trigger star formation in a molecular cloud while a weak or high ionizing flux would erode or disperse a molecular cloud of initial condition as a Bonnor-Ebert sphere (Bonnor 1956) The initial temperature of the prolate cloud was set as 60 K, considering the warm nature of the surroundings of stars, similar to that used in the previous RDI simulations for the formation of different types of BRCs (Miao et al 2006(Miao et al , 2009(Miao et al , 2010 and collapse of molecular cloud in FUV radiation field (Nelson & Langer 1999).…”
Section: Ionizing Radiation Flux and The Initial Temperaturementioning
confidence: 99%
“…It allows us to study how the shell resulting from the collect and collapse scenario may be perturbed. The possibility to have localized density gradients has been extensively studied with the radiation-driven-implosion scenario (Mackey & Lim 2010;Bisbas et al 2011;Gritschneder et al 2009) and more recently within a turbulent media (Gritschneder et al 2010). In this work, we first want to focus on more simple and schematic situations in which the physical processes at work can be identified and studied more easily.…”
Section: Forming Pillarsmentioning
confidence: 99%
“…This scenario has been studied in detail with numerical simulations for years (see Lefloch & Lazareff 1994;Williams et al 2001;KesselDeynet & Burkert 2003). Recently, Bisbas et al (2011) and Gritschneder et al (2009) looked at the implosion of isothermal spherical clouds with smoothed particle hydrodynamics (SPH) codes. Using a grid code, Mackey & Lim (2010) produced elongated structures from dense spherical clumps using the shadowing effects of these structures.…”
Section: Introductionmentioning
confidence: 99%